Diodorus' mythistory and the pagan mission historiography and culture-heroes in the first pentad of the Bibliotheke - Sulimani, Iris. (Mnemosyne, Supplements, 2011)
The traditional Diodoran scholarship has been challenged in the last decades by a revisionist approach, which concentrates on Diodorus Siculus' contribution rather than on his lost sources. Building on that approach, this book focuses on the Bibliotheke's first pentad, which has usually been neglected as a subject of research, and explores the author's depictions of journeys made by gods and culture-heroes. A thorough investigation of his historiographical methods and his representation of mythical figures demonstrates that the mythological narrative is not only an essential part of his universal history, but also an important supplement to our knowledge of Hellenistic civilization, especially its mentality and historical geography.